Substituents Effects to the Electrochemical, and In Situ Spectroelectrochemical Behavior of Metallophthalocyanines: Electrocatalytic Application for Hydrogen Evolution Reaction - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2010)
This study describes the effects of the number of fluoro substituents to the electrochemical, in situ spectroelectrochemical, and electrocatalytic activities of metallophthalocyanines for the hydrogen evolution reaction. Tuning of the number of fluoro groups shifts the redox processes and affects the aggregation tendencies of the complexes. An in situ electrocolorimetric method was applied to investigate the color of the electrogenerated anionic and cationic forms of the complexes. Cobalt phthalocyanines incorporated into Nafion film on a glassy carbon electrode decreases the overpotential of the working electrode for H+ reduction. The number and position of the electron withdrawing substituents and nature of the metal center change the electrocatalytic activities for the hydrogen evolution reaction in aqueous solutions.
Keywords: Phthalocyanine; Spectroelectrochemistry; Chromaticity diagram; Electrocatalyst; Hydrogen evolution reaction; FLUORINATED COPPER PHTHALOCYANINE; LIGHT-EMITTING DEVICES; METAL-PHTHALOCYANINES; COBALT PHTHALOCYANINES; OXYGEN REDUCTION; PROTON REDUCTION; COMPLEXES; FILM; DERIVATIVES; WATER